Role of nonspecific risk factors in atopic dermatitis - D. Sh. Macharadze; E. A. Rassanova; T. A. Ruzhentsova; A. V. Galanina; V. S. Malyshev (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
The increasing prevalence of atopic dermatitis (AD) over recent decades suggests that environmental factors play an important role in the etiology and pathogenesis of the disease. Nonspecific factors refer to external (or exposomal) factors and include human and natural factors that influence the health of a population: for example, the socioeconomic status of the patient; climate, including air temperature, exposure to ultraviolet radiation, air pollution; and living in a city or rural area. Although studies have shown the influence of these factors on the course of AD, in general, none of them significantly increases or decreases the risk of developing the disease. This review briefly discusses studies on the role of nonspecific environmental risk factors and their impact on the course of AD in children and adults.